Downregulation of KSR1 in pancreatic cancer xenografts by antisense oligonucleotide correlates with tumor drug uptake - Zhang, Jianjun (2008)
While antisense oligonucleotide (AS-ODN) technology holds promise for the treatment of cancer, to date there have been no clinical successes. Unfortunately, current assays are not sufficiently sensitive to measure tissue ODN levels. Hence it has not been possible to ascertain whether treatment failures result from failure of drug delivery. To investigate the relationship between drug uptake and therapeutic effect, we developed an ultrasensitive noncompetitive hybridization-ligation enzyme-linked immunosorbent assay (NCHL-ELISA) to quantify Kinase Suppressor of Ras1 (KSR1) AS-ODN drug uptake in plasma and tumor tissues. In mice harboring PANC-1 pancreatic cancer xenografts and continuously infused with AS-ODN, our ELISA detects plasma and tumor KSR1 AS-ODN levels over an extended range, from 0.05 nM to 20 nM. Using this sensitive assay, we demonstrate that KSR1 repression in pancreatic cancer xenografts correlates highly with AS-ODN uptake into tumor tissues. In contrast, plasma drug levels do not correlate with tumor drug content or target downregulation. These studies indicate the efficacy of our ELISA, and suggest that tumor biopsy material will need to be procured to estimate the potential of this antisense technology.